Bendix Model 12-101A Mass Spectrometer - Bendix Corporation (1970)
Two views of a Bendix Model 12-101A Time-of-Flight Mass Spectrometer, with view of the ion source, vacuum system, and assorted control panels and gauges. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers